2007
DOI: 10.1111/j.1751-3928.2007.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Geochemistry of the Buerkesidai and Kuoerzhenkuola Gold Deposits in the Sawuershan Region, Xinjiang Uigur Autonomous Region, Northwest China

Abstract: The Sawuershan region, one of the important gold metallogenic belts of Xinjiang, is located in the western part of the Kalatongke island arc zone of north Xinjiang, NW China. There are two gold deposits in mining, namely the Kuoerzhenkuola and the Buerkesidai deposits. Gold ores at the Kuoerzhenkuola deposit occur within Carboniferous andesite and volcanic breccias in the form of gold-bearing quartz -pyrite veins and veinlet groups containing native gold, electrum, pyrite, pyrrhotite and chalcopyrite. Gold ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…These authors also inferred that gold was transported as AueS complex and precipitated under reducing condition. Zeng et al (2007) reported, d 34 S values ranging from 1.5& to 3.5&, and averaging 1.9&, suggesting that the ore-forming sulphur were sourced from magmas that fed subvolcanic intrusions and surface volcanism. The estimated d 18 O water values vary from 1.8& to 3.2&, with corresponding dD values of from À84& to À89&, which are indicative that the ore-forming fluidsystem is a mixture of magmatic and meteoric waters.…”
Section: Kuoerzhenkuolamentioning
confidence: 95%
See 1 more Smart Citation
“…These authors also inferred that gold was transported as AueS complex and precipitated under reducing condition. Zeng et al (2007) reported, d 34 S values ranging from 1.5& to 3.5&, and averaging 1.9&, suggesting that the ore-forming sulphur were sourced from magmas that fed subvolcanic intrusions and surface volcanism. The estimated d 18 O water values vary from 1.8& to 3.2&, with corresponding dD values of from À84& to À89&, which are indicative that the ore-forming fluidsystem is a mixture of magmatic and meteoric waters.…”
Section: Kuoerzhenkuolamentioning
confidence: 95%
“…Hydrothermal alteration includes kaolinitization, silicification, sericitization, chloritization, epidotization, alunitization and fluoritization. Because of the strong kaolinitization and alunitization the deposit is considered a high sulphidation-style epithermal system (Shen et al, , 2008Zeng et al, 2007). All the gold orebodies are contained within these alteration zones.…”
Section: Kuoerzhenkuolamentioning
confidence: 99%
“…These authors also inferred that gold was transported as Au-S complex and precipitated under reducing condition. Zeng et al (2007) reported, d 34 S values ranging from 1.5 to 3.5%, and averaging 1.9%, suggesting that the oreforming sulfur were sourced from magmas that fed subvolcanic intrusions and surface volcanism. ore-forming fluid system is a mixture of magmatic and meteoric waters.…”
Section: Kurzhenkula Gold Depositmentioning
confidence: 95%
“…The alteration includes kaolinitization, silicification, sericitization, chloritization, epidotization, alunitization and flouritization. Because of the strong kaolinite and alunite alteration the deposit was considered to be a HS-style epithermal system Zhang 1998;Shen et al 2004Shen et al , 2007Shen et al , 2008aZeng et al 2005Zeng et al , 2007.…”
Section: Kurzhenkula Gold Depositmentioning
confidence: 99%
“…The source of ore‐forming fluid is one of the key issues to the ore genesis. In the past 30 years, noble gas isotopes, particularly He and Ar, have been widely used to discriminate the origin and evolution history of the ore‐forming fluids, and considerable progress has been made (Simmons et al, ; Stuart et al, ; Hu et al, ; Shen et al, , ; Zeng et al, , ). Since the rare gas is chemically inert, therefore remaining unchanged during the geological evolution, and ore‐forming fluids from various sources have different isotopic composition characteristics, these can reflect the original information of the origin and evolution of the ore‐forming fluids.…”
Section: Introductionmentioning
confidence: 99%